ANALYSIS OF ACCOUNTING TREATMENT OF 3 KG LPG GAS INVENTORY BASED ON PSAK NO. 14. 14 AT SPPBE PT. DELTA GASINDO SEJAHTERA - halim, syalomitha; Lambey, Robert; Maradesa, Djeini (ACCOUNTABILITY, 2024)
Syalomitha Halim. Analysis of Accounting Treatment of 3 kg LPG Gas Inventory Based on PSAK No. 14 at SPPBE PT Delta Gasindo Sejahera. Accounting Economics Study Program, Faculty of Economics and Business, Sam Ratulangi University, 2024. Inventory is one of the company's important assets that has a very big influence on its operational activities. In addition, the inventory account is very important because inventory is a very important asset of the company and contributes to the creation of revenue in the company's financial statements. This study aims to analyze the application of accounting treatment of 3 kg LPG gas inventory at PT Delta Gasindo Sejahtera's LPG Bulk Filling and Transportation Station (SPPBE) based on Statement of Financial Accounting Standards (PSAK) No. 14. The research methodology used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The results showed that PT Delta Gasindo Sejahtera has implemented PSAK No. 14 in recording and reporting 3 kg LPG gas inventory consistently. However, there are several obstacles in the inventory management process that need to be improved, such as a less integrated information system and inaccuracies in recording the amount of inventory. This study provides recommendations for companies to improve accounting information systems and conduct training for employees to better Keywords : Inventory Accounting, PSAK No. 14